Study of incidence, risk factors and immediate outcome of hypoglycemia in neonates admitted in NICU - Ansari, Aatif; Savaskar, S. V.; Tamboli, Moin; S. N., Pushpa (International Journal of Contemporary Pediatrics, 2023)
Background: Hypoglycemia is the most common metabolic problem occurring in newborns which is associated with poor neurologic outcome. The present study was conducted to determine the incidence, risk factors and immediate outcome of hypoglycemia in neonates. Methods: The present study was conducted on 3776 babies born with risk factors for hypoglycemia in NICU. Screening for blood glucose level of study subjects were done at 2, 4, 6,12,24,48,78 hours of life, twice daily and whenever symptomatic by using glucometer. Babies were followed up till discharge. Incidence, risk factors and immediate outcome of hypoglycemia were assessed. Appropriate tests were applied. Results: Incidence of hypoglycemia was 9.93% among high-risk neonates and overall incidence was 5.20%. 54.13% were males. 45% were preterm, 78.7% neonates were LBW. 53.07% were born to primiparous mother, 20.5% to diabetic mothers and 28.5% to hypertensive mothers. 16.8% had perinatal asphyxia, 14.66% new-born had underlying RDS. 48.5% were symptomatic, most common being lethargy 52.75% followed by jitteriness 43.41%, convulsion in 63 (34.62%). Preterm and LBW were significantly associated with mortality. Most common underlying comorbidities associated with deaths were sepsis (59.10%), RDS (45.46%), perinatal asphyxia (13.64%) and meconium aspiration syndrome (4.55%). Conclusions: Neonates with one or more risk factors for hypoglycemia should be screened irrespective of symptoms within 72 hours of life. Focused counselling on early initiation of breast feeding will reduce the incidence of hypoglycemia and its complications.